Peran Penyuluh Perikanan Dalam Pengembangan Sektor Perikanan Di Kabupaten Aceh Utara - Safrida Safrida; T. Makmur; Hafid Fachri (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. North Aceh Regency is an area which has great potential in fishery sector. Training for the fishery sector holds an important role in developing fishery sector in an area. The fishery trainers are expected to gain knowledge, skills, as well as better attitudes of the fishermen and fish farmers. The objective of this study is to discover the role as well as the effectiveness of fishery trainers in developing fishery sector in North Aceh Regency. Based on the result of the analysis using FGD method, it can be concluded that fishery trainers have the role in delivering fishery information, distributing fishery production facilities, and processing and marketing the fishery products. This training which was participated by fishermen and fish farmers with great enthusiasm is effective in developing fishery sector in North Aceh Regency. It can be seen from the improvement of the ability of the fishermen and fish farmers who participated in the training and theirability to implement innovations derived from the training activities.